Slip-Line Solutions of Some Axi-Symmetric Problems of Plastic Compression of Cylinders and Rings - Grzymkowski, M.; Mróz, Z. (Engineering Transactions, 1976)
Two axi-symmetric problems are treated for a perfectly plastic model: indentation of cylindrical punches into a circular plate and compression of rings between rigid plates. Static and kinematic fields are determined by integrating numerically characteristic equations for stress and velocity. Bounds on limit indentation and compression pressures are computed and compared with experimentally determined pressures.